Molybdenum trioxide negative electrode material for aqueous ion battery and preparation method of molybdenum trioxide negative electrode material

The nanoflower-shaped α-MoO3 negative electrode material was prepared by solvent-thermal method, which solved the structural stability and cyclic performance problems of the molybdenum trioxide negative electrode material in water-based ion batteries, and achieved the improvement of electrochemical performance with high specific capacity and long life. It is suitable for water-based ion batteries.

CN120261555APending Publication Date: 2025-07-04CENT SOUTH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510484922.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-17
Publication Date
2025-07-04

AI Technical Summary

Technical Problem

The existing molybdenum trioxide anode materials for water-based ion batteries have poor conductivity and high charge density of embedded ions, resulting in poor structural stability, slow kinetics, low actual specific capacity, poor cycle performance, and easy agglomeration of conventional nanomorphology, making it difficult to maintain structural stability and improve comprehensive performance for a long time.

Method used

The nanoflower-shaped α-MoO3 negative electrode material was prepared by solvothermal method. Through the cooperation of the molybdenum source and the etchant, a three-dimensional structure supported by multiple nanosheets is formed, with a high specific surface area and a large number of pores, avoiding agglomeration and enhancing structural stability.

Benefits of technology

The actual specific capacity and circulation performance of water-based ion batteries have been improved, the specific capacity of 50-100mAh/g has a cycle life of 150-200 cycles, and has good electrochemical activity and stability. It is suitable for water-based aluminum ion and zinc ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure BDA0005363857940000081
    Figure BDA0005363857940000081
Patent Text Reader

Abstract

The invention discloses a molybdenum trioxide negative electrode material for an aqueous ion battery and a preparation method of the molybdenum trioxide negative electrode material. The molybdenum trioxide negative electrode material for the aqueous ion battery is nanoflower-shaped alpha-MoO3 composed of a plurality of nanosheets, and the nanosheets are mutually staggered and supported to generate a large number of pore structures. The preparation method is simple and easy to implement, the product is high in purity and uniform in distribution, the nanoflower-shaped microstructure greatly increases the specific surface area and shortens the ion / electron migration path, meanwhile, a large number of pore structures are provided, volume expansion in the charging and discharging process is effectively relieved, and the performance of the material is improved. And when being used as the negative material of the aqueous ion battery, the composite material has relatively high actual specific capacity and good cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and particularly relates to a molybdenum trioxide negative electrode material for aqueous ion batteries and a preparation method thereof. Background Art

[0002] Aqueous ion batteries, etc., are considered to be one of the energy storage devices that are more in line with the concept of sustainable development due to their high safety, fast ion migration rate, rich resources, and low cost. The negative electrodes currently used in aqueous ion batteries can be divided into two types: metal negative electrodes and intercalation compound negative electrodes. Among them, intercalation compounds have better development prospects because they can avoid serious problems such as hydrogen evolution corrosion, passivation, and dendrites in the aqueous electrolyte of metal negative electrodes, which seriously affect the cycle life and reversibility of the electrodes. In particular, the layered transition metal oxide - orthorhombic molybdenum trioxide α-MoO3 has the advantages of high theoretical specific capacity, stable chemical properties, and low cost compared with other intercalation materials, and is an ideal intercalation negative electrode material for aqueous ion batteries.

[0003] However, in practical applications, due to the poor conductivity of α-MoO3 and the high charge density of the intercalated ions, its structural stability is poor and the kinetics is slow, which in turn leads to problems such as low actual specific capacity and poor cycle performance. Regarding its low specific capacity, morphology control is a simple and efficient method. By preparing α-MoO3 into a nano-morphology with a high specific surface area, more energy storage active sites and shorter ion migration paths can be provided, thereby having a higher actual specific capacity and faster ion diffusion kinetics. However, the current morphology control of molybdenum trioxide negative electrodes for aqueous ion batteries mainly focuses on conventional one-dimensional or two-dimensional nano-structures (such as nano-dots, nano-wires, nano-sheets, etc.). Such morphologies are prone to agglomeration during the cycling process due to their high surface energy, which easily causes the inactivation of active substances and thus leads to insufficient cycle performance. The too-high specific surface area will also cause too many side reactions. The morphology control with a three-dimensional structure, such as nano-leaves, nano-microspheres, and nano-flowers, not only retains the advantage of high specific surface area of low-dimensional nano-morphologies, but also can reduce the agglomeration phenomenon. In particular, the large number of pore structures existing in its structure can effectively alleviate the volume effect generated during the ion deintercalation process of the material, greatly enhancing its structural stability. However, there are not many reports on the three-dimensional morphology control of α-MoO3 in the negative electrode material of aqueous ion batteries and related simple and efficient preparation methods.

[0004] In summary, through morphology control, the electrochemical performance of α-MoO3 as the negative electrode of aqueous ion batteries can be effectively improved. However, the conventional low-dimensional nano-morphology control is prone to agglomeration during the cycling process, cannot maintain the structural stability of the material for a long time, and is not conducive to the improvement of its comprehensive performance such as specific capacity and cycle performance. Summary of the Invention

[0005] One of the objectives of the present invention is to provide a molybdenum trioxide negative electrode material for aqueous ion batteries. The material is α-MoO3 with a nano-flower-like microstructure. Its three-dimensional flower-like structure enables the material to have a high actual specific capacity and good cycling performance when used as the negative electrode of aqueous ion batteries.

[0006] Another objective of the present invention is to provide a preparation method for the molybdenum trioxide negative electrode material for aqueous ion batteries.

[0007] The present invention provides a molybdenum trioxide negative electrode material for aqueous ion batteries. The negative electrode material is composed of nano-flower-like α-MoO3 with a diameter of 2 - 3 μm. The nano-flower is composed of multiple α-MoO3 nano-sheets, and flexible branches are formed between the nano-sheets. The diameter of the nano-sheets is 0.5 - 1.5 μm, and the thickness is 20 - 100 nm. The nano-sheets support each other in an interlaced manner and have a large number of pore structures, which can provide a specific surface area of 10 - 50 m 2 / g.

[0008] The nano-flower-like structure with a three-dimensional structure has good dispersibility and is not prone to agglomeration. Flexible branches are formed between multiple α-MoO3 nano-sheets, increasing the specific surface area, shortening the ion / electron migration path, and providing a large number of pore structures, effectively alleviating the volume expansion during charge and discharge.

[0009] The present invention also provides a preparation method for the molybdenum trioxide negative electrode material for aqueous ion batteries, including the following steps:

[0010] S1. Place the molybdenum source in a solvent according to a set ratio to obtain solution A;

[0011] S2. Take etching agent B and add it dropwise into solution A according to a set ratio, and stir at room temperature until it becomes clear to obtain solution C;

[0012] S3. Transfer solution C to a reaction kettle for solvothermal reaction. After the reaction is completed and cooled to room temperature, take out the product, wash it several times with deionized water and ethanol respectively, then centrifuge to collect the precipitate, and finally dry the obtained precipitate at 60 °C for 12 h to obtain the molybdenum trioxide negative electrode material for aqueous ion batteries.

[0013] Further, in step S1, the molybdenum source is one of molybdenum acetylacetonate, molybdenum isopropoxide, molybdenum(II) acetate dimer, bis(ethylbenzene)molybdenum, molybdenum 2-ethylhexanoate, and molybdenum tricarbonyl cycloheptatriene.

[0014] In the present invention, an organic complex of molybdenum is selected as the molybdenum source to generate molybdenum trioxide. Compared with other inorganic molybdenum sources, it has a lower solvothermal temperature and a shorter solvothermal time, which can avoid particle agglomeration caused by high-temperature calcination and reduce energy consumption. At the same time, this organic molybdenum complex does not introduce metal ions other than molybdenum, and the product purity is relatively high (99.5%).

[0015] Further, in step S1, the content of the molybdenum source in solution A is 4 - 8 g / L.

[0016] If the addition amount of the molybdenum source is too low, the reaction cannot proceed smoothly and the yield is low; if it is too high, it cannot be completely dissolved, affecting the product morphology.

[0017] Further, in step S1, the solvent is at least one of tetrahydrofuran, 2-methyltetrahydrofuran, dioxane, dichloromethane, dichloroethane, N,N-dimethylformamide, dimethyl sulfoxide, and acetonitrile.

[0018] The solvents selected in the present invention are all aprotic polar organic solvents, which have good solubility for the organic molybdenum source, can make it more evenly dispersed; at the same time, they can form complexes with the molybdenum ions dissociated from the molybdenum source to achieve uniform nucleation.

[0019] Further, in step S2, the etchant B is at least one of hydrogen peroxide and concentrated sulfuric acid, concentrated nitric acid, and hypochlorous acid, and the ratio of hydrogen peroxide to the acid is 10:(0 - 10).

[0020] In the etchant selected in the present invention, the role of the added hydrogen peroxide is to dissolve and collapse the surface of the initial molybdenum trioxide microspheres to generate peroxymolybdates, and the peroxymolybdates regenerate molybdenum trioxide nanosheets, which accumulate on the surface of the microspheres and self-assemble into nanoflowers; the added acids all have certain oxidizing properties and can be used to accelerate the reaction process and shorten the reaction time.

[0021] Further, in step S2, the volume ratio of the etchant B to the solvent in step S1 is (1 - 5):100.

[0022] The content of the etchant selected in the present invention plays an important role in the formation of nanoflower-like α-MoO3. If the content of the etchant is too low, the flower-like structure is incompletely formed and the specific surface area is too low; if the content is too high, the petals become thinner and the flower-like structure will collapse.

[0023] Further, in step S2, the stirring duration is 50 - 70 min.

[0024] The above stirring process mainly allows molybdenum acetylacetonate to be fully dissolved in the solvent and completely mixed with the etchant. If the stirring time is too short, the molybdenum source cannot be completely dissolved, affecting the reaction progress.

[0025] Further, in step S3, the solvothermal reaction temperature is 140 - 200 °C, and the reaction time is 1 - 12 h.

[0026] The present invention synthesizes the target product by the solvothermal method, which is simple and efficient. By controlling the reaction temperature and time within the scope of the present invention, nano-flower-shaped α-MoO3 with a high specific surface area and a relatively complete and uniform flower-like morphology can be prepared. The reaction temperature and reaction time have a great influence on the morphology of the product. If the temperature is too high or the time is too long, the etching agent will over-etch and destroy the formed flower-like structure; if the temperature is too low or the time is too short, the flower-like structure will not be completely formed and the specific surface area will be relatively low.

[0027] Advantages of the present invention:

[0028] (1) The molybdenum trioxide negative electrode material for aqueous ion batteries provided by the present invention is α-MoO3 with a nano-flower-shaped structure. It has a large specific surface area, can provide more active sites and shorter ion / electron migration paths, has a larger contact area with the electrolyte, and has higher electrochemical activity. There are also a large number of pore structures in its structure, endowing the material with a more stable structure, which can be used to alleviate the volume effect during the charge and discharge cycle process, effectively enhancing the cycle performance of the material. Compared with other low-dimensional nano-morphologies, the actual specific capacity can be increased by 50 - 100 mAh / g, and the cycle life reaches 150 - 200 cycles;

[0029] (2) The negative electrode material for aqueous ion batteries provided by the present invention has excellent electrochemical performance when used as the negative electrode material for aqueous aluminum ion batteries and aqueous zinc ion batteries. When cycling at a certain current density, it has a high initial charge and discharge specific capacity, good cycle performance, and stable Coulomb efficiency (above 99.5%);

[0030] (3) Since the negative electrode material for aqueous ion batteries of the present invention is prepared by the solvothermal method, its nano-flower-shaped structure remains intact, and agglomeration and caking that easily occur in the conventional solid-phase method will not occur. The product has high purity and uniform distribution. The synthesis method is simple, the conditions are mild, the yield is high, and the materials used are simple and easy to obtain, facilitating industrial production. Description of the Drawings

[0031] Figure 1 Scanning electron microscope image of a molybdenum trioxide negative electrode material for aqueous ion batteries prepared in Example 1 magnified 50,000 times;

[0032] Figure 2 Scanning electron microscope image of a molybdenum trioxide negative electrode material for aqueous ion batteries prepared in Example 1 magnified 10,000 times. Detailed Embodiments

[0033] For the convenience of understanding the present invention, the present invention will be described in more comprehensive and detailed manner below in conjunction with preferred embodiments, but the protection scope of the present invention is not limited to the following specific embodiments.

[0034] Unless otherwise defined, all the technical terms used hereinafter have the same meanings as commonly understood by those skilled in the art. The technical terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the protection scope of the present invention.

[0035] Except as otherwise specified, all kinds of reagents and raw materials used in the present invention are commercially available products or products that can be prepared by well-known methods.

[0036] Example 1

[0037] Take 0.5 g of molybdenum acetylacetonate and place it in a beaker. Measure 75 ml of tetrahydrofuran and add it to form a mixed solution. Then measure 3 ml of hydrogen peroxide (the volume ratio of hydrogen peroxide to tetrahydrofuran is 4:100) and slowly add it to the mixed solution. Stir evenly at room temperature of 25 °C for 1 h until all the added molybdenum acetylacetonate is dissolved and the solution becomes clear.

[0038] Transfer the obtained clear solution to a reaction kettle, react at 180 °C for 6 h. After the reaction is completed, let it cool naturally to room temperature, take it out, wash it 3 times each with deionized water and absolute ethanol, then collect by centrifugation. Finally, place the obtained precipitate in a vacuum drying oven and dry it at 60 °C for 12 h to obtain the product.

[0039] Weigh 0.21 g of the above-prepared material, mix it with conductive carbon black and binder (PVDF) according to the mass ratio of 7:2:1, grind it in a mortar until there are no obvious particles, add N-methylpyrrolidone (NMP) as a solvent and stir until the slurry is evenly mixed. Coat the stirred slurry on a titanium foil, dry it at 60 °C for 12 h, then cut it into a disc with a diameter of 13 mm, denoted as electrode sheet A.

[0040] Prepare 2 mol / L zinc trifluoromethanesulfonate solution B and 5 mol / L aluminum trifluoromethanesulfonate solution C respectively. Take a piece of high-purity zinc plate, make it into a disc with a diameter of 13 mm as the positive electrode and the negative electrode, use solution B as the electrolyte, and use glass fiber as the separator to assemble a 2023-type button symmetric battery. At a current density of 0.2 mA / cm2, perform constant current charging for 1 h. The obtained negative electrode is the Zn-Al alloy, denoted as electrode sheet D.

[0041] Finally, use the electrode sheet A prepared in Example 1 as the negative electrode of the aqueous aluminum-ion battery, use solution C as the electrolyte, and assemble a 2023-type half-cell in the order of button battery positive electrode shell, electrode sheet A, glass fiber separator, solution C, electrode sheet D, gasket, spring piece, button battery negative electrode shell, and perform electrochemical performance testing on it on the Land system.

[0042] The results show that the overall morphology of the prepared anode material presents a nano peony flower shape, with an average diameter between 2 and 2.5 μm, and good dispersion between the nano flowers; its petals are composed of nanosheets with a diameter between 0.8 and 1.5 μm and a thickness between 50 and 100 nm. There are a large number of pores between the nanosheets, forming a good framework structure. When the battery is at a current density of 0.2 A / g, the initial discharge specific capacity is 240 mAh / g, and the discharge specific capacity is 100 mAh / g after 135 cycles; at a current density of 0.4 A / g, the initial discharge specific capacity is 270 mAh / g, and the discharge specific capacity is 100 mAh / g after 213 cycles.

[0043] Comparative Example 1

[0044] This comparative example is basically the same as Example 1, except that the volume ratio of hydrogen peroxide to tetrahydrofuran added is 6:100, that is, 4.5 ml. Assembled into a battery according to the method of Example 1, the initial discharge specific capacity at a current density of 0.2 A / g is 175 mAh / g, and the discharge specific capacity is 100 mAh / g after 110 cycles; at a current density of 0.4 A / g, the initial discharge specific capacity is 200 mAh / g, and the discharge specific capacity is 100 mAh / g after 134 cycles.

[0045] Comparative Example 2

[0046] This comparative example is basically the same as Example 1, except that the volume ratio of hydrogen peroxide to tetrahydrofuran added is 0.5:100, that is, 0.375 ml. Assembled into a battery according to the method of Example 1, the initial discharge specific capacity at a current density of 0.2 A / g is 150 mAh / g, and the discharge specific capacity is 100 mAh / g after 75 cycles; at a current density of 0.4 A / g, the initial discharge specific capacity is 140 mAh / g, and the discharge specific capacity is 100 mAh / g after 50 cycles.

[0047] Comparative Example 3

[0048] This comparative example is basically the same as Example 1, except that the volume ratio of hydrogen peroxide to tetrahydrofuran added is 0:100, that is, 0 ml. Assembled into a battery according to the method of Example 1, the initial discharge specific capacity at a current density of 0.2 A / g is 124 mAh / g, and the discharge specific capacity is 100 mAh / g after 33 cycles; at a current density of 0.4 A / g, the initial discharge specific capacity is 110 mAh / g, and the discharge specific capacity is 100 mAh / g after 20 cycles.

[0049] Comparative Example 4

[0050] This comparative example is basically the same as Example 1, except that the solvothermal temperature is 120 °C. Assemble the battery according to the method of Example 1. The initial discharge specific capacity at a current density of 0.2 A / g is 196 mAh / g, and the discharge specific capacity after 112 cycles is 100 mAh / g; at a current density of 0.4 A / g, the initial discharge specific capacity is 223 mAh / g, and the discharge specific capacity after 138 cycles is 100 mAh / g.

[0051] Comparative Example 5

[0052] This comparative example is basically the same as Example 1, except that the solvothermal temperature is 220 °C. Assemble the battery according to the method of Example 1. The initial discharge specific capacity at a current density of 0.2 A / g is 201 mAh / g, and the discharge specific capacity after 110 cycles is 100 mAh / g; at a current density of 0.4 A / g, the initial discharge specific capacity is 235 mAh / g, and the discharge specific capacity after 140 cycles is 100 mAh / g.

[0053] Perform constant current charge-discharge tests on Example 1 and Comparative Examples 1-5 at a current density of 0.2 A / g, as shown in Table 1.

[0054] Table 1 Constant current charge-discharge test results of Example 1 and Comparative Examples 1-5 at a current density of 0.2 A / g

[0055]

[0056] Perform constant current charge-discharge tests on Example 1 and Comparative Examples 1-5 at a current density of 0.4 A / g, as shown in Table 2.

[0057] Table 2 Constant current charge-discharge test results of Example 1 and Comparative Examples 1-5 at a current density of 0.4 A / g

[0058]

[0059] Example 2

[0060] Take 0.5 g of molybdenum acetylacetonate and place it in a beaker. Measure 75 ml of 2-methyltetrahydrofuran and add it to form a mixed solution. Then measure 3 ml of hydrogen peroxide and slowly add it to the mixed solution. Stir evenly at room temperature of 25 °C for 1 h until all the added molybdenum acetylacetonate is dissolved and the solution becomes clear.

[0061] Transfer the obtained clear solution to a reaction kettle and react at 180 °C for 6 h. After the reaction is completed, let it cool naturally to room temperature, take it out, wash it 3 times each with deionized water and absolute ethanol, then centrifuge and collect it. Finally, place the obtained precipitate in a vacuum drying oven and dry it at 60 °C for 12 h to obtain it.

[0062] Weigh 0.21 g of the above-prepared material, mix it with conductive carbon black and binder (PVDF) in a mass ratio of 7:2:1, grind it in a mortar until there are no obvious particles, add N-methylpyrrolidone (NMP) as a solvent and stir until the slurry is evenly mixed. Coat the stirred slurry on a titanium foil, dry it at 60 °C for 12 h, and then cut it into circular pieces with a diameter of 13 mm, denoted as electrode A.

[0063] Prepare a 3 mol / L zinc triflate solution B. Take a piece of high-purity zinc plate and make it into a circular piece with a diameter of 13 mm, denoted as electrode C.

[0064] Finally, use the electrode A prepared in Example 2 as the negative electrode of the aqueous zinc-ion battery, and solution B as the electrolyte. Assemble a 2023-type half-cell in the order of button battery positive electrode case, electrode A, glass fiber separator, solution B, electrode C, gasket, spring piece, and button battery negative electrode case, and conduct electrochemical performance tests on it on the Land system.

[0065] The results show that the overall morphology of the prepared negative electrode material presents a nano-hydrangea shape, with an average diameter of about 2 μm, and good dispersion between the nano-flowers; its petals are composed of nanosheets with a diameter of 0.5 - 0.8 μm and a thickness of 20 - 50 nm. The nanosheets are closely stacked, and there are a large number of pore structures. At a current density of 0.2 A / g, the initial discharge specific capacity of the battery is 236 mAh / g, and the discharge specific capacity is 100 mAh / g after 200 cycles; at a current density of 0.4 A / g, the initial discharge specific capacity is 255 mAh / g, and the discharge specific capacity is 100 mAh / g after 220 cycles.

[0066] Comparative Example 6

[0067] This comparative example is basically the same as Example 2, except that the volume ratio of hydrogen peroxide to tetrahydrofuran added is 6:100, that is, 4.5 ml. Assemble the battery according to the method of Example 2. At a current density of 0.2 A / g, the initial discharge specific capacity is 150 mAh / g, and the discharge specific capacity is 100 mAh / g after 120 cycles; at a current density of 0.4 A / g, the initial discharge specific capacity is 183 mAh / g, and the discharge specific capacity is 100 mAh / g after 133 cycles.

[0068] Comparative Example 7

[0069] This comparative example is basically the same as Example 2, except that the volume ratio of hydrogen peroxide to tetrahydrofuran added is 0.5:100, that is, 0.375 ml. Assemble the battery according to the method of Example 2. The initial discharge specific capacity at a current density of 0.2 A / g is 124 mAh / g, and the discharge specific capacity after 112 cycles is 100 mAh / g; at a current density of 0.4 A / g, the initial discharge specific capacity is 132 mAh / g, and the discharge specific capacity after 120 cycles is 100 mAh / g.

[0070] Comparative Example 8

[0071] This comparative example is basically the same as Example 2, except that the volume ratio of hydrogen peroxide to tetrahydrofuran added is 0:100, that is, 0 ml. Assemble the battery according to the method of Example 2. The initial discharge specific capacity at a current density of 0.2 A / g is 112 mAh / g, and the discharge specific capacity after 50 cycles is 100 mAh / g; at a current density of 0.4 A / g, the initial discharge specific capacity is 119 mAh / g, and the discharge specific capacity after 30 cycles is 100 mAh / g.

[0072] Comparative Example 9

[0073] This comparative example is basically the same as Example 2, except that the solvothermal temperature is 120 °C. Assemble the battery according to the method of Example 2. The initial discharge specific capacity at a current density of 0.2 A / g is 183 mAh / g, and the discharge specific capacity after 131 cycles is 100 mAh / g; at a current density of 0.4 A / g, the initial discharge specific capacity is 215 mAh / g, and the discharge specific capacity after 155 cycles is 100 mAh / g.

[0074] Comparative Example 10

[0075] This comparative example is basically the same as Example 2, except that the solvothermal temperature is 220 °C. Assemble the battery according to the method of Example 2. The initial discharge specific capacity at a current density of 0.2 A / g is 196 mAh / g, and the discharge specific capacity after 143 cycles is 100 mAh / g; at a current density of 0.4 A / g, the initial discharge specific capacity is 201 mAh / g, and the discharge specific capacity after 164 cycles is 100 mAh / g.

[0076] Perform constant current charge-discharge tests on Example 2 and Comparative Examples 6-10 at a current density of 0.2 A / g, as shown in Table 3.

[0077] Table 3 Constant current charge-discharge test results of Example 2 and Comparative Examples 6-10 at a current density of 0.2 A / g

[0078]

[0079] The constant current charge-discharge tests were carried out on Example 2 and Comparative Examples 6-10 at a current density of 0.4 A / g, as shown in Table 4.

[0080] Table 4 Constant current charge-discharge test results of Example 2 and Comparative Examples 6-10 at a current density of 0.4 A / g

[0081]

[0082] By comparing the cycling performance of the aqueous aluminum-ion batteries in Example 1 and Comparative Examples 1-5 and the cycling performance of the aqueous zinc-ion batteries in Example 2 and Comparative Examples 6-10, it can be found that the initial discharge specific capacity and cycling performance of the negative electrode of this aqueous ion battery composed of nano-flower-like α-MoO3 have been significantly improved.

[0083] The above embodiments of the present invention are merely examples for clearly illustrating the technical solutions of the present invention, rather than limitations on the specific implementation manners of the present invention. Any modifications, equivalent replacements, and improvements made within the spirit and principle of the claims of the present invention shall be included within the protection scope of the claims of the present invention.

Claims

1. A molybdenum trioxide negative electrode material for an aqueous ionic battery, characterized in that, The negative electrode material is composed of nano-flower-shaped α-MoO3; the nano-flowers are composed of a number of α-MoO3 nano-sheets, and flexible branches are formed between the nano-sheets.

2. The molybdenum trioxide negative electrode material for aqueous ionic batteries according to claim 1, characterized in that, The diameter of the nano-flower-like α-MoO3 is 2-3 μm; the diameter of the α-MoO3 nano-sheets is 0.5-1.5 μm, and the thickness is 20-100 nm; the nano-sheets support each other in a staggered manner and have a large number of pore structures, which can provide a specific surface area of 10-50 m 2 / g.

3. A preparation method of the molybdenum trioxide negative electrode material for the aqueous ionic battery according to any one of claims 1 or 2, characterized in that, It includes the following steps: S1. Place the molybdenum source in a solvent according to a set ratio to obtain solution A; S2. Take the etchant B according to a set ratio and drop it into solution A, stir at room temperature until it becomes clear to obtain solution C; S3. Transfer solution C to a reaction kettle for solvothermal reaction; after the reaction ends and cools to room temperature, take out the product, wash it several times with deionized water and ethanol respectively, then centrifuge to collect the precipitate, and finally dry the obtained precipitate at 60 °C for 12 h to obtain the molybdenum trioxide negative electrode material for the aqueous ion battery.

4. The preparation method according to claim 3, characterized in that, In step S1, the molybdenum source is one of molybdenum acetylacetonate, molybdenum isopropoxide, molybdenum(II) acetate dimer, bis(ethylbenzene)molybdenum, molybdenum 2-ethylhexanoate, and molybdenum tricarbonyl cycloheptatriene.

5. The preparation method according to claim 3, characterized in that, In step S1, the content of the molybdenum source in solution A is 4-8 g / L.

6. The preparation method according to claim 3, wherein In step S1, the solvent is at least one of tetrahydrofuran, 2-methyltetrahydrofuran, dioxane, dichloromethane, dichloroethane, N,N-dimethylformamide, dimethyl sulfoxide, and acetonitrile.

7. The preparation method according to claim 3, wherein, In step S2, the etchant B is hydrogen peroxide and at least one of concentrated sulfuric acid, concentrated nitric acid, and hypochlorous acid, and the ratio of hydrogen peroxide to the acid is 10:(0-10).

8. The preparation method according to claim 3, characterized in that, In step S2, the volume ratio of the etchant B to the solvent in step S1 is (1-5):

100.

9. The preparation method according to claim 3, wherein In step S2, the stirring duration is 50-70 min.

10. The preparation method according to claim 3, characterized in that, In step S3, the solvothermal reaction temperature is 140-200 °C, and the reaction time is 1-12 h.